A REVIEW ON NATURAL POLYMER - Gupta, Akanksha; Sharma, Natasha; Khinchi, M. P.; Agrawal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2013)
Pharmaceutical formulation contains two ingredients one is the active ingredient and other is a polymer. A polymer help in the manufacturing of dosage form and it also improves physicochemical parameters of the dosage form. Polymers play an important role in any dosage form. They influence drug release and should be compatible, non-toxic, stable, economic etc. They are broadly classified as natural polymers and synthetic polymers. They have wide range of applications so selection of polymer is the main step in designing any dosage form. Nowadays, due to many problems associated with drug release and side effects manufacturers are inclined towards using natural polymers. Natural polymers are basically polysaccharides so they are biocompatible and without any side effects. This review discusses various natural polymers, their advantages, their extraction process and role of natural polymers in designing novel drug delivery systems.